Developing GIS Database for Support Fire Prevent and Fighting in Govap District – Ho Chi Minh City Base on Network Analyst - Quy, Bui Ngoc; Thanh, Bui Quang (VNU Journal of Science: Earth and Environmental Sciences, 2017)
This paper refers to the study, using network analysis in developing a database to support the Fire prevent and fighting (FPF). The network analysis system will support the fire protection agencies determine the fire point location, find the optimal route to approach the fire location, find the location of water points near fire or define the scope of fire protection service stations, ... in order to maneuver planning when the problem occurred. Base on the analysis, we develop an empirical database in Go Vap District - Ho Chi Minh City and deployed some solutions to support the fire protection agencies. Keywords Fire Prevent and Fighting (FPF), Network Analyst, GIS, Go Vap References [1] ESRI, (2006), GIS Technology and Applications for the Fire Service, An ESRI® White Paper. [2] http://www.govap.hochiminhcity.gov.vn [3] Nguyễn Thị Thoa (2014), Nghiên cứu khả năng ứng dụng công nghệ GIS hỗ trợ công tác chữa cháy khu vực đô thị, Đồ án tốt nghiệp Trường đại học Mỏ - Địa chất. [4] Nguyễn Thị Thoa và nnk (2014), “Nghiên cứu ứng dụng công nghệ GIS trong công tác chữa cháy khẩn cấp ở quận Cầu Giấy, Thanh Xuân và Đống Đa, Hà Nội” Tạp Chí Khoa học Trường đại học Cần Thơ, Phần A: Khoa học Tự nhiên, Công nghệ và Môi trường số 34, tr.54-65. [5] Bộ Tài Nguyên và Môi Trường (2012), Quy định Quy chuẩn kỹ thuật quốc gia về chuẩn thông tin địa lý cơ sở (QCVN 42: 2012/BTNMT), Hà Nội. [6] ESRI, (2010). Network Analyst tutorial, Exercise book.